Comparison of Antigenicity Between Local and Massachusetts Strains of Infectious Bronchitis Virus using Indirect ELISA Test - Rahmahani, Jola; Akbar, Daniswara Irwanza; Suwarno, Suwarno (Universitas Airlangga, 2022)
The aim of this study was to compare the antigenicity between the whole virus and protein S of both local strain I-147 and Massachusetts strain of Infectious bronchitis virus with indirect ELISA. We used 10 positive serums from post vaccinated chickens for further reaction with four groups of antigens in this study that are: P1) S protein (spike glycoprotein) antigen of local strain IB virus; P2) S protein (spike glycoprotein) antigen of Massachusetts strain IB virus; P3) whole virus antigen of local strain IB virus; P4) whole virus antigen of Massachusetts strain IB virus. The results of this research are Optical Density (OD) values of each treatment, then to be analyzed using One Way ANOVA and followed by Duncan Multiple Range Test 5%. The results show that there are differences between the antigenicity of the whole virus and S protein in both local strain and Massachusetts strain of IB virus. The whole virus antigen of both strains has a significant difference (p<0.05) with the S protein antigen in both strains. Specifically, the whole virus antigen of Massachusetts strain has the highest OD among the other groups.